Qualitative Researches In Social Sciences - Upadhyay, Prakash; KC, Vikash Kumar (Janapriya Journal of Interdisciplinary Studies, 2017)
Qualitative social science research is fundamentally embedded in grounded theory concerned with how the social world is interpreted, realized, understood and experienced, or produced. Qualitative investigation seeks answers to their questions in the realistic world. They congregate what they see, hear and read from the people and places and from events and activities and their main purpose are to learn about some aspects of the social world and to generate new understandings that can be used by that social world. The main objective of this study is the interpretation of social world especially of cultures and people’s life-ways rather than seeking causal explanations for social-cultural practices. Nevertheless, in very rapidly changing information dominated globalized world, innovative traditions of the perception of emerging local and global contexts and realities need to be exposed and accepted as well as practiced in qualitative social science research. Janapriya Journal of Interdisciplinary Studies, Vol. III (December 2014), page: 54-61